2006
DOI: 10.1097/01.hjh.0000226201.73065.14
|View full text |Cite
|
Sign up to set email alerts
|

Transient receptor potential channels in essential hypertension

Abstract: This study points to an important role of TRPCs in essential hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
52
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 49 publications
1
52
0
Order By: Relevance
“…The specific targeted sequence of TRPC5 was sense, 5Ј-GGAGGCUGAGAUCUACUAUtt-3Ј; and antisense, 5Ј-AUAGUAGAUCUCAGCCUCCtg-3Ј (Liu et al, 2006). ECs at 80% confluence were incubated with siRNA duplex of TRPC5 (20 nM final concentration) for 24 h using the transfection kit (RNAiFect, Qiagen) and following the manufacturer's protocol.…”
Section: Down-regulation Of Trpc Mrnamentioning
confidence: 99%
“…The specific targeted sequence of TRPC5 was sense, 5Ј-GGAGGCUGAGAUCUACUAUtt-3Ј; and antisense, 5Ј-AUAGUAGAUCUCAGCCUCCtg-3Ј (Liu et al, 2006). ECs at 80% confluence were incubated with siRNA duplex of TRPC5 (20 nM final concentration) for 24 h using the transfection kit (RNAiFect, Qiagen) and following the manufacturer's protocol.…”
Section: Down-regulation Of Trpc Mrnamentioning
confidence: 99%
“…Dietrich et al 4 reported that TRPC6-deficient mice with consecutively increased TRPC3 channel expression developed higher blood pressure. Liu et al 5,6 and Thilo et al 7 reported increased TRPC3 protein expression and increased TRPC3 transcripts in peripheral blood monocytes from patients with essential hypertension compared to normotensive control subjects. The expression of TRPC3 in human vascular endothelium has not been associated with malignant hypertension yet.…”
mentioning
confidence: 99%
“…In addition, increased TRPC3 and TRPC5 expression in monocytes of patients with essential hypertension, a subsequent storeoperated Ca 2+ influx, and increased 1-oleoyl-2-acetyl-snglycerol-induced cation influx in monocytes of patients with essential hypertension were observed [61]. Liu et al [1] compared the expression level and function of TRPCs between essential hypertensive patients and normotensive control subjects. They demonstrated increased TRPC3 and TRPC5 protein expression and an increase in the gadolinium/calcium-influx ratio via TRPCs in monocytes of patients with essential hypertension [1].…”
Section: Trp Channel Subtype C Dysfunction Promotes the Development Omentioning
confidence: 99%
“…Liu et al [1] compared the expression level and function of TRPCs between essential hypertensive patients and normotensive control subjects. They demonstrated increased TRPC3 and TRPC5 protein expression and an increase in the gadolinium/calcium-influx ratio via TRPCs in monocytes of patients with essential hypertension [1]. Furthermore, they demonstrated an increase in TRPC3 expression in VSMCs and aortic tissues and TRPC3-related Ca 2+ influx in VSMCs from spontaneously hypertensive rats (SHRs), which was associated with enhanced contraction in vasculature from SHRs compared with the normotensive WKY rats [4].…”
Section: Trp Channel Subtype C Dysfunction Promotes the Development Omentioning
confidence: 99%
See 1 more Smart Citation